Participatory GIS Approach to Assessing Building Vulnerability to Tsunamis in Pangandaran Regency - Ratri Ma'rifatun Nisaa'; Junun Sartohadi; Djati Mardiatno (Forum Geografi, 2021)
Some cities in Indonesia which are located on Southern Java Island are susceptible to tsunamis. However, the application of participatory GIS for the assessment of building vulnerability to tsunamis remains rarely evaluated. The aims of this research are 1) to obtain the parameters of building vulnerability to tsunamis using the participatory approach, and 2) to evaluate the results of building vulnerability assessment using participatory GIS. A tsunami inundation map was constructed based on numerical modelling using the Hawke's Bay equation. Participatory approaches were taken to establish the parameters that affect the vulnerability of buildings to tsunamis using in-depth interviews. Respondents were selected using the purposive sampling technique. A geographic information system (GIS) was then applied to build a geodatabase and to perform analysis. The results show that six parameters were obtained from local people’s participation, namely building materials, the number of stories of the buildings , orientation, preservation condition, building row, and natural barriers. All the parameters were identified and interpreted using aerial photos. A field survey was conducted to complete the information on building characteristics. Many buildings near the beach were classified as having high and moderate vulnerability. The main benefit of participatory GIS is that the role of the community makes a significant contribution to providing vulnerability information. It also raises public awareness and improves preparedness for disaster risk management. The drawback is that parameters based on participatory approaches are dynamic and may be different in other areas.